Efficacy of dexmedetomidine as adjuvant to bupivacaine in femoral-sciatic nerve blocks in dogs undergoing tibial plateau levelling osteotomy (TPLO). (January 2023) - Di Bella, Caterina; Pennasilico, Luca; Botto, Riccardo; Salvaggio, Alberto; Galosi, Margherita; Staffieri, Francesco; Piccionello, Angela Palumbo
Abstract: The aim of this randomized, prospective clinical study was to evaluate the efficacy of dexmedetomidine combined with bupivacaine on sciatic and femoral nerve blocks in dogs. Thirty dogs were selected for elective unilateral tibial plateau levelling osteotomy, and each subject was assigned randomly to receive perineural bupivacaine 0.5% (0.1 mL/kg) and intramuscular dexmedetomidine (0.5 μg/kg) in the BDs group, perineural bupivacaine 0.5% (0.1 mL/kg) plus dexmedetomidine (0.5 μg/kg) in the BDloc group, and perineural bupivacaine 0.5% (0.1 mL/kg) plus intramuscular administration of saline solution the in Bupi group. Nerve blocks were guided by electrolocation. The main intraoperative parameters were registered 10 min before the start of surgery (BASE) and during the skin incision (SKIN), the osteotomy (BONE) and the suture (SUTURE). At 2, 4, 6, 8, 10, 15, 20 and 24 h after blocks, the Glasgow Composite Pain scale (GPCs) was used to identify the degree of pain during the postoperative period. Patients with scores ≥5/20 received rescue analgesia and were excluded. Furthermore, heart rate, mean arterial pressure, footstep capacity, reaction to wound touch and femoral and sciatic skin sensitivity were registered. Parametric data were compared at each time point of the study with the one-way ANOVA for repeated measures and Fisher's test for yes/no variables analysis ( p < 0.05). No subject required intraoperative rescue analgesia. In BDloc group, the GCPs score was <5/20 for all dogs at all times of the study, and 70% of dogs did not need systemic analgesia. In the Bupi and BDs groups, 100% of subjects achieved a score ≥ 5/20 between 8 and 10 h after the blocks, and 100% of subjects showed femoral and sciatic skin sensitivity and required rescue analgesia within 10 h. Our results showed that the addition of dexmedetomidine as an adjuvant to bupivacaine in SF blocks may prolong the sensory block and ensure sufficient analgesia for up to 24 h in dogs undergoing TPLO surgery. Highlights: Orthopedic surgery causes severe pain during the peri-operative period in dogs. Peripheral nerve blocks are a useful tool in surgical pain management. Dexmedetomine, used as adjuvant, can increase the duration of peripheral blocks. Bupivacaine plus dexmedetomidine can achieve pain management for 24 h in dogs.